2013
DOI: 10.3168/jds.2011-4930
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of meloxicam in lame dairy cows undergoing resection of the distal interphalangeal joint

Abstract: The objective was to evaluate the analgesic efficacy of pre- and postoperative administration of meloxicam on the postsurgical convalescence period of lame dairy cows undergoing resection of the coffin joint. In a blinded, placebo-controlled, explorative clinical trial, 19 lame German Holstein-Friesian cows weighing 536 ± 98 kg (mean ± SD) and aged 5.7 ± 2.8 yr were included. All cows suffered from unilateral lameness due to septic arthritis of the coffin joint. Lame cows were randomly allocated to either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
1
20
1
3
Order By: Relevance
“…It was previously reported that calves treated with 1 mg/kg flunixin at the time of lameness induction with amphotericin B were more active than untreated controls (Schulz et al, 2011). In a recent study it was reported that cows that received 0.5 mg/ kg MEL IV once daily for 4 d following resection of the distal interphalangeal joint took more steps per hour than control cattle (Offinger et al, 2013). The results of the present study support this observation.…”
Section: Step Countsupporting
confidence: 82%
See 1 more Smart Citation
“…It was previously reported that calves treated with 1 mg/kg flunixin at the time of lameness induction with amphotericin B were more active than untreated controls (Schulz et al, 2011). In a recent study it was reported that cows that received 0.5 mg/ kg MEL IV once daily for 4 d following resection of the distal interphalangeal joint took more steps per hour than control cattle (Offinger et al, 2013). The results of the present study support this observation.…”
Section: Step Countsupporting
confidence: 82%
“…Recently it was reported that plasma cortisol concentrations and lameness scores were significantly reduced in cows that received 0.5 mg/kg MEL IV once daily for 4 d following resection of the distal interphalangeal joint (Offinger et al, 2013). This finding contradicts the results of the present study that found no association between MEL administration and a reduction in cortisol concentrations in calves after induction of lameness.…”
Section: Serum Cortisol Concentrationscontrasting
confidence: 57%
“…Generally, professionals agree that major surgeries such as amputation or resection of the distal interphalangeal joint in case of advanced stages of claw horn lesions demand local anesthesia and administration of analgesics to control postoperative pain (Desrochers and St Jean, 1996;Heppelmann et al, 2009;Becker et al, 2013;Offinger et al, 2013). However, assuming that in most instances lame cows are treated by professional claw trimmers or stockmen, therapeutic claw trimming in cows with nonadvanced claw horn lesions is normally done under restraint without any sedation, anesthesia, or analgesia Whay et al, 2005;Becker et al, 2014).…”
Section: Short Communicationmentioning
confidence: 95%
“…Once every 4 wk, 4 cows [1 nonlame cow (control = group C) and 3 lame cows (lame = group L)] were selected and moved to the lame cow pen. Criteria for inclusion in group C were that cows were in second lactation, clinically healthy and not lame [(locomotion score ≤1, according to Offinger et al (2013)]. The criteria for inclusion in group L were that cows were in second or later lactation, clinically healthy except for the presence of lameness [locomotion score >1, according to Offinger et al (2013)] and had a claw horn lesion of one hind claw.…”
Section: Selection Of Cowsmentioning
confidence: 99%